Validations and psychological properties of a simplified Chinese version of pain anxiety symptoms scale (SC-PASS) - Zhou, Xiao-Yi (Medicine (Baltimore), 2017)
The Pain Anxiety Symptoms Scale (PASS) has been developed to evaluate pain anxiety, which leads to avoidance of daily activities and normal movements. However, a simplified Chinese version of PASS is still not available. Physicians are not aware of which patients are prone to anxiety, and what the risk factors are. To cross-culturally adapt the PASS into a simplified Chinese version and test the reliability and validity. Factors affecting pain anxiety were also explored. The PASS was first translated into a simplified Chinese version according to a forward-backward method. Then, validations were tested including content validity, construct validity, and reliability. Content validity was analyzed by response trend. Construct validity was analyzed by confirmatory factor analysis (CFA), exploratory factor analysis, and priori hypotheses testing. Reliability was analyzed by internal consistency and test–retest reliability. Risk factors of catastrophizing were analyzed by performing multivariate liner regression. A total of 219 patients were included in the study. The scores of items were well distributed. Both CFA and exploratory factor analysis suggested a 2nd-order, 4-factor model, accounting for 65.42% of the total variance according to principle component analysis. SC-PASS obtained good reliability with a Cronbach α = 0.92 and ICC = 0.90. College education, long pain duration, and both married and divorced status were risk factors. Factors reduced pain-related anxiety were no medication assumption, female sex, widowed status, non-Han ethnicity, and having no religious belief. The SC-PASS was applicable in Chinese patients and it was suitable for the clinical uses in mainland China.